Ambulatory 5-Fluorouracil Infusors: Experiences of Patients Diagnosed with Gastrointestinal Cancer - Huber, Tracey (My University, 2023)
Background: Treatment for advanced gastrointestinal (GI) cancer frequently requires continuous administration of 5-Fluorouracil (5-FU) over 46-hours through an ambulatory infusor. While convenient, evidence suggests that infusors may impact day-to-day activities and health-related quality of life (HRQL). There is limited research on the impact of this technology on patients' health, or if current practices meet their health needs. This study aimed to explore patient experiences receiving 5-FU through an ambulatory infusor at home for GI cancers. Methods: A qualitative descriptive design was employed. Participants were patients diagnosed with a GI cancer who had received 5-FU through an ambulatory infusor for 46 hours within the last twelve months at a cancer centre in Southwestern Ontario. Semi-structured interviews were conducted by telephone, transcribed verbatim, and analyzed using content analysis methods to code data and identify relevant patterns and themes. Results: Ten patients with four types of GI cancers participated in the study. Their experience with ambulatory infusors ranged from 8 to 54 treatment cycles. Common themes included the psychosocial impact of having an infusor, the intense work of patient self-management, and supporting patients in self-management. Conclusions: Results indicate that use of an infusor may have a more negative effect on patients' mental health than previously understood. Psychosocial assessment and support should be routinely utilized, and significant efforts should be made to prepare patients for living with an infusor. Streamlining services and reducing the number of cancer care-related appointments would also lessen the burden currently placed on patients.
Keywords: Infusor, 5-Fluorouracil, Patient Experience, Gastrointestinal Cancer, Nursing Role